(untitled) (Journal of Hama University, 2024)
This study aims to reveal the prevalence of circling disease Caused by Listeria monocytogenes in sheep flocks in Hama governorate. This study was conducted on 203 samples of sheep dung, which suffer from the appearance of the typical symptoms of circling disease, located within the different geographical regions of Hama Governorate. Through the use of discriminatory media, and appropriate biochemical tests, in detecting the infection of circling disease, Caused by Listeria Monocytogenes, The results of bacterial isolation and biochemical tests showed that 28 samples were positive of 203 samples of sheep dung, with total prevalence of 13.80%. The upper prevalence of circling disease in sheep flocks was in Tal Al-Tuott region as reported prevalence 16.27%, while it was less prevalence of circling disease in sheep flocks was in the AL Sheikh Hilal region as 10.00%.